Przesłanki organizacyjno-kompetencyjne wykonywania mandatu posła i radnego: [Exercise of a mandate of a member of the the Diet and of a councilor - some premises concerning organization and competence] (Studia Prawnicze / The Legal Studies, 1981)
Representation — the Diet and people’s councils, and particularly the people who sit in these organs, i.e. members of the Diet and councillors, play the most important role in the process of deepening and developing socialist government by the people. It depends upon their active, open and critical attitude and activity that the citizens appreciate the role and functioning of the system of representation in a socialist state. The relation of a member of the Diet and of a councillor with the voters and especially: making reports concerning the acti- vity of the Diet and of the people’s councils, activating the iniciative of the- population, making use by the members of the Diet and the councillors of various ideas and remarks of the citizens in the works of parlament and that of people’s councils, guarantees not only proper law-making and controlling activity of the representation but also helps to overcome the idea of dychotomy ’'authority - society”, "they - we”, "state - private” still existing in the consciousness of many citizens.The structure of competence of the Diet and of people’s councils, the activity of the members of the Diet and of councillors, their open and critical attitude during the debates on drafts of laws and resolutions or in contacts with the representatives of administration, their stubbornness in requiring elimination of persons of bad faith or unapt from the managerial posts, constitute the best testimony of our polemic attitude to the concepts advanced in the west such as “technocracy”, “expertocracy” and other similar ideas proclaiming the “dusk of democracy” in a modern society.Execution of a mandate of a member of the Diet or of a councillor is in a general way regulated in electoral regulations, in the rules of the Diet, in the' law on people’s councils and in the rules of people’s councils. These acts ex- pressly define the rights of members of the Diet and of councillors sitting in chamber or in people’s councils and their organs, the principles of participation- in debates and in decision-making determined by the rules of procedure of the debates, the forms of exercising the duties before the voters and the rights- which serve them not only in the chamers and in people’s councils but also beyond them.Legal regulation in this domain seems sufficient. However, it also seems necessary to create even better socio-political conditions for the realization of the mandates of members of the Diet and of councillors, to secure proper under- standing and importance to their interventions and propositions made to the- authorities and offices, to ameliorate the forms of cooperation with the autho- rities and various organizations of working people. This concerns also making' use of some rights of the members of the Diet and of councillors as far as their controlling functions are concerned, that is to say, stimulating their activity in questioning and making interpolations, in presenting their views and their proper observations based on and gained owing to the relations with the voters.Legal and systematic structure of the principle of superiority of the Diet and of people’s councils - which also means specific position of a member of the Diet and of a councillor, their role, rights and duties - results to a great extent from specific tasks and competences as well as from the forms of activity of these organs. Plenary sessions called “sessions of the Diet” and “sessions of the people’s councils” should be distinguished here since only there laws are passed and this means that only then they act as organs of state authority. This particular position and type of activity of the Diet and of people’s councils can be reconstructed from many provisions of the Constitution and from laws re- gulating the procedure, forms and extent of the functions such as: law- and: resolution-making, controlling the organs of administration and their professional apparatus, inspiring and leading in showing directions of activity for execu- tory and managerial organs.